PENGARUH PROMOTIONAL MIX TERHADAP KEPUTUSAN PEMBELIAN TIKET PESAWAT GARUDA INDONESIA AIRLINES PADA PT. GARUDA INDONESIA MALL LEMBUSWANA SAMARINDA - rangga setiawan (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
Rangga Setiawan. The effect of Promotional Mix on Purchase   Decision Tickets Garuda Indonesia Airlines at the PT. Garuda Indonesia Mall Lembuswana Samarinda. (Guidance of Mrs Dr. Hj. Rahmawati, SE., MM   and Mrs. Dr. Hj. Sri Wahyuni, SE., M.Si).               The purpose of this study was to determine the influence of Promotional Mix on Purchase Decision. This research was conducted at the PT. Garuda Indonesia Mall Lembuswana Samarinda sampling method using random sampling and aksidential sampling, population numbers used for 2 years  as many as 1.931 people and be used samples of 100 people who were in PT. Garuda Indonesia Mall Lebuswana Samarinda. The data in this study using primary data, interviews and questionnaires. Hypothesis test used in this study is Multiple Linear Regression using SPSS version 22.               The results of this study show that: 1) Advertising has a positive and significant effect on Purchase Decision at PT. Garuda Indonesia Mall Lebuswana Samarinda, 2) Personal Selling has a positive and significant effect on Purchase Decision at PT. Garuda Indonesia Mall Lebuswana Samarinda, 3) Sales Promotion has a positive and significant effect on Purchase Decision at PT. Garuda Indonesia Mall Lebuswana Samarinda, 4) Publicity Advertising has a positive and significant effect on Purchase Decision at PT. Garuda Indonesia Mall Lebuswana Samarinda, 5) and variable Advertising as variables are positive and significant effect of the most dominant effect on Purchase Decision at PT. Garuda Indonesia Mall Lebuswana Samarinda. Key words: Promotional Mix, and Purchase Decision